Advancement in measuring the hydraulic conductivity of porous asphalt pavements. (20th September 2021) - Giuliani, F.; Petrolo, D.; Chiapponi, L.; Zanini, A.; Longo, S.
Highlights: A novel air permeameter has been developed for conductivity in porous pavements. Laboratory tests with glass beads and in situ experiments have been performed. The water to air conductivity ratio predicted by dimensional analysis was verified. A relationship between an equivalent length path and thickness of plates is proposed. Abstract: The measurement of the in situ hydraulic conductivity of porous asphalt pavements, K, is a matter of practical interest; however, there are cases where current techniques are difficult to use. Several methods are documented in literature, mainly based on permeameters with water as fluid. Using water has its advantages, as it is straightforwardly related to the drainage problem during rain storms, but it also involves some major issues, especially on field studies. For instance, the time necessary to reach the steady state is too long and the necessary amount of water could not be available. In addition, non-repeatability and hysteresis phenomena can occur, also due to air bubbles confined in the porous matrix. In the present paper, we describe a novel test method for measuring K using air at low pressure as fluid. The proposed permeameter was first tested in the laboratory, in order to (i) validate the theoretical relationships between K H 2 O and K air, and (ii) define a model to evaluate an equivalent length scale for asphalt pavements, L eq, as a function of the thickness of the porous layer (this is useful when one-dimensional formulations are adopted in the case of three-dimensional plates or in situ measurements). Finally, the protocol and methodology were validated on two sites in Italy (Monza, Milan, and Poviglio, Reggio Emilia) where K air was measured by the air field permeameter, and compared with K H 2 O, measured by a standard falling head permeameter. The technique allows the determination of the hydraulic conductivity on the basis of the ratio between pressure difference and flow rate, and of L eq .